Validation of the ABC Method for Gastric Cancer Risk Stratification Across Helicobacter pylori Infections With Diverse CagA Status and Subtypes in Brazil - Luis Masuo Maruta; Asuka Furukawa; Heinrich Bender Kohnert Seidler; Aloisio Felipe‐Silva; Keisuke Uchida; Daisuke Kobayashi; Kurara Yamamoto; Junko Minami; Masaki Sekine; Minako Takagi; Renato Takayuki Hassegawa; Eduardo Koji Marchi Ogawa; et al. (Cancer Medicine, 2025)
ABSTRACT Background Gastric cancer survival rates vary across countries due to differences in access to early diagnostic testing and healthcare quality. Endoscopy, though accurate, is not feasible for mass screening. The ABC method, which combines serum Helicobacter pylori (Hp) antibody and pepsinogen tests, has shown promise for gastric cancer risk stratification in Japan. However, its applicability in populations with diverse CagA status and subtypes remains uncertain. Materials and Methods This prospective study in Brazil evaluated the performance of the ABC method in an endoscopy‐referred cohort with a heterogeneous distribution of Hp CagA status and subtypes. A recently validated immunohistochemical method was applied to formalin‐fixed paraffin‐embedded gastric biopsy samples to assess Hp infection, CagA expression, and CagA subtypes. Gastric pathology was evaluated using the updated Sydney System and OLGA/OLGIM staging and correlated with serum Hp antibody and pepsinogen levels in 586 patients, including 122 Japanese Brazilians. Results Immunohistochemistry achieved a 98% success rate (577/586). The prevalence of Hp infection was 48%, with Western‐type CagA(+) (26%) and CagA(−) (18%) strains predominating. East Asian‐type CagA(+) strains (4%) were observed primarily among Japanese Brazilians, particularly in second‐generation individuals. Gastric pathology and serum markers differed significantly across CagA status and subtypes. Despite these differences, the ABC method's negative predictive values (NPVs) across all groups other than Group A (negative for both tests) remained high (97%/97% or 98%/100% for detecting OLGA/OLGIM stages ≥ II or ≥ III, and 94%/98% or 99%/100% for detecting antrum/corpus inflammation scores ≥ 2 or 3, respectively). Conclusions These findings demonstrate the clinical relevance of CagA diversity for gastric cancer risk assessment. Although limited to an endoscopy‐referred cohort, the ABC method reliably identified low‐risk individuals (Group A) and may help reduce unnecessary endoscopies in screening programs, regardless of CagA status and subtypes. Broader, population‐based studies are needed to validate its generalizability and optimize its implementation.